Evaluation of the Hospital Management Information System (SIMRS) at Rafflesia Hospital Bengkulu - Arifin, Ismail; Heltiani, Nofri; Desmiany Duri, Iin (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2023)
Hospital Management Information System (SIMRS) is a communication information technology system that processes hospital services. Rafflesia Bengkulu Hospital has been implementing SIMRS since 2021. Currently there has not been an evaluation of the features contained in SIMRS so that this will result in not achieving service improvements, not achieving efficiency and slowing down service to patients. The aim of this research is to describe the implementation of the hospital management information system (SIMRS) at Rafflesia Hospital Bengkulu. The research used is a descriptive method, namely a method that aims to describe the description of the implementation of the hospital management information system (SIMRS). The subjects of this research were 10 respondents. It is known from the evaluation results of the system performance aspect that research results show that the system performance is good by 80% and the system performance is not good by 20%. 90% of the information produced is good, 10% of the information produced is not good. data security is good as much as 60% and not good as much as 40%. It is necessary to develop the SIMRS menu display so that it can support all services, and also to develop the system so that it does not experience frequent errors (errors). And notifications/warnings need to be given if SIMRS is accessed by unauthorized parties, so that the system can be controlled properly and is not misused by unauthorized parties.